KESALAHAN BERBAHASA DALAM KARANGAN DESKRIPSI BERBAHASA MANDARIN MAHASISWA PRODI PENDIDIKAN BAHASA MANDARIN - Aditya, Rendy (Paramasastra: Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2017)
The approach used in this study is a qualitative approach, because this study aims to describe the linguistic fault lines in the descriptive essay done by the students of Chinese Education Department ofÂ  University state of Surabaya academic year 2012. In this research, there are 53 essays written by 53 respondent. Data analysis was initiated by identifying the mistakes in syntax and lexicon of descriptive essay in Mandarin, then classify these forms of error into linguistic taxonomy, and concluded the factors that cause errors speak.The results of this study consists of three parts. The first part is finding a syntax error in the form of a descriptive essay in Mandarin, which forms a syntax error in the preparation of fungtor language of Mandarin, some 5 grains fault error. Furthermore, the use of particles in Mandarin improper, some 9 points of error. The latter syntax error is improper preparation of the sentence as much as 82 grains of error. Where errors in grammar occur due to the authors make a mistake that the order of words in reverse. In addition there is also a mistake lexicon, namely in the form of improper use of the word as much as 134 grains contained errors. The latter is a global and a local fault. Globally there are 8 points errors and locally there are 6 items mistake. Factors causing the linguistic fault lines obtained from interviews of respondents stated that when studying Mandarin, the most difficult thing to learn is the grammar. This isproved by the number of 8 respondents who answered grammar is the hardest less onto learn. Then the tone and word pronunciation difficulties as many as seven people. The latter as much as 3 respondents said things that are difficult to study in Mandarin is writing Chinese characters. Recently, there were14 respondents who were not able to give an example of the full text of some kind of sentence filed by the researcher to the respondents.